วิวัฒนาการละครใน - ขวัญใจ คงถาวร (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This dissertation is a qualitative research aiming 1) to study the evolution of Lakhon Nai and 2) to examine the pattern of I-nao in Rattanakosin period. This document research was conducted through related printed media, videos, in-depth interview to experts, and observation. The scope of study covers 1) background and evolution related to Lakhon Nai from Ayudha period to Rattanakosin period, 2) pattern of Lakhon Nai showing the story of I-nao from the past until 2016 at Bunditpatanasilpa Institute and Fine Arts Department, Ministry of Culture. The findings show that the term "Lakhon Nai" was coined in Rattanakosin period; before that, this kind of performance was variously called including "Lakhon Nai Borichakkri", "Lakhon Luang", "Lakhon Pooying", and "Lakhon Kangnai". All of them conveyed the same meaning as "classical plays performed by women in royal court which was under the king’s patronage". The first evidence of Lakhon Nai was found in Bunnowat Khumchan (Bunnowat Poem) of Ayudha period. It mentioned Anirut and I-nao (originally from Indonesian "Panji") which were both Lakhon Nai Borichakkri meaning "plays of the king". After the ruin of Ayudha in 1767, this kind of plays spread to other places such as in Myanmar. This point was the origin of Yodia or Yodaya plays of Myanmar. In Thonburi period, Lakhon Nai was called "Lakhon Pooying" (female plays). This plays were support by either King Taksin or city rulers but those supported by the city rulers needed to be permitted by King Taksin. In the beginning of Rattanakosin period in which a lot of restoration work was required, King Rama I created "Tamra Ram" (The Collection of Classical Dances) including the dancing styles from Ayudha period as a national heritage. Then, in King Rama II period, a new version of plays was composed for the Lakhon Nai. This revision included new dancing style and pose. The performers in the Lakhon Nai from this period became masters of Lakhon Nai later on. Therefore, this pattern become the master pattern for later Lakhon Nai. In King Rama IV period, prohibition and restriction of Lakhon Nai was aborted. Noblemen imitated the royal practice which resulted in expansion of Lakhon Nai to noblemen and ordinary people. It can be seen that the most important factors of the evolution of lakhon Nai were policy and taste of the kings and rulers. External factors such as foreign influence, economy and society in each period also affect the evolution. The traditional pattern was the important foundation of the development and transformation of Lakhon Nai in later period such as Lakhon Dukdamban and has progressed to the creation of dancing convention at the present.